1996
DOI: 10.1074/jbc.271.45.28024
|View full text |Cite
|
Sign up to set email alerts
|

Lysine-based Cluster Mannosides That Inhibit Ligand Binding to the Human Mannose Receptor at Nanomolar Concentration

Abstract: In search of synthetic high affinity ligands for the mannose receptor, we synthesized a series of lysinebased oligomannosides containing two (M 2 L) to six (M 6 L 5 ) terminal ␣-D-mannose groups that are connected with the backbone by flexible elongated spacers (16 Å). The synthesized cluster mannosides were all able to displace binding of biotinylated ribonuclease B and tissuetype plasminogen activator to isolated human mannose receptor. The affinity of these cluster mannosides for the mannose receptor was co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
55
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(58 citation statements)
references
References 32 publications
(23 reference statements)
3
55
0
Order By: Relevance
“…This work will focus firstly on the synthetic objective of coupling a mannose residue with affinity for the MR to a luminescent lanthanide chelate and secondly on investigating the effect of the mannose hydroxyls on emission intensity. Substrates with two or more mannose residues are known to show high affinity for the mannose receptor, particularly when linked in a branched formation [12,13]. For the purpose of this investigation, single -D-mannose residues and simple Eu(III) chelates were employed to avoid complicating the analysis of the mannose residue on emission intensity.…”
Section: Introductionmentioning
confidence: 99%
“…This work will focus firstly on the synthetic objective of coupling a mannose residue with affinity for the MR to a luminescent lanthanide chelate and secondly on investigating the effect of the mannose hydroxyls on emission intensity. Substrates with two or more mannose residues are known to show high affinity for the mannose receptor, particularly when linked in a branched formation [12,13]. For the purpose of this investigation, single -D-mannose residues and simple Eu(III) chelates were employed to avoid complicating the analysis of the mannose residue on emission intensity.…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that the affinity of MRs was enhanced with mannose valencies, increasing from 2 to 6 terminal mannose residues in synthesized series of lysine-based cluster oligomannosides. [60] Espuelas et al studied interaction of plain liposomes and mannosylated liposomes with immature human dendritic cells (iDC). [61,62] Our results are in accordance with published data and we confirmed that in defined conditions for in vivo experiments, dimannosylated liposome formulations were as efficient as tetramannosylated liposome formulations.…”
Section: Determination Of the Entrapment Efficiency Of Ova And Immunomentioning
confidence: 99%
“…While it is well acknowledged that, on the macroscale, these multivalent interactions strongly influence ligand-receptor binding kinetics and the biological responses they govern, the microscale patterning of ligands on substrates can also have a profound effect on multivalent kinetics and are able to further modulate biological signaling [4] . In particular, ligand-receptor clusters can dramatically increase interactions between cell and substrate; not only the valency, but spatial factors such as branching mode and the localized clustering of groups are important [5][6][7] in influencing binding and downstream signaling processes [8,9] . Still, despite the prevalence of patterned ligand presentation in cell biology and its demonstrated significance on 2D tissue engineering formats [10,11] , it remains largely unappreciated by those who design nanoparticle synthetic systems intended to interact with cells.…”
Section: Introductionmentioning
confidence: 99%